God's arbiters: Americans and the Philippines, 1898 - 1902 - Harris, Susan K. (Imagining the Americas, 2011)
Introduction: A Christian nation -- section 1: American narratives -- Citizenship and the Philippines debates : the religious factor -- Citizenship and the Philippines debates: the racial factor -- section 2: Creating citizens -- A Connecticut Yankee in the Philippines -- The national Christian -- section 3: The eyes of the world -- "The White man's burden," the Philippines, and the Anglo-American alliance -- Saxon eyes and Barbaric souls: responses to the American annexation of the Philippines in Europe and Latin America -- Noli me tangere: Filipino responses to annexation